2021
DOI: 10.3389/fbioe.2021.633028
|View full text |Cite
|
Sign up to set email alerts
|

A High-Efficiency Artificial Synthetic Pathway for 5-Aminovalerate Production From Biobased L-Lysine in Escherichia coli

Abstract: Bioproduction of 5-aminovalerate (5AVA) from renewable feedstock can support a sustainable biorefinery process to produce bioplastics, such as nylon 5 and nylon 56. In order to achieve the biobased production of 5AVA, a 2-keto-6-aminocaproate-mediated synthetic pathway was established. Combination of L-Lysine α-oxidase from Scomber japonicus, α-ketoacid decarboxylase from Lactococcus lactis and aldehyde dehydrogenase from Escherichia coli could achieve the biosynthesis of 5AVA from biobased L-Lysine in E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…Therefore, the precursor levels in the B. methanolicus strains should not be a limiting factor for production of 5AVA. The RaiP-mediated production is mainly utilized in the L-lysine bioconversion approach, utilizing E. coli strains as whole-cell biocatalysts (Cheng et al, 2018(Cheng et al, , 2020(Cheng et al, , 2021 where high concentrations of the precursor were used; for example, the molar yield of 0.942 was obtained from 120 g l −1 Llysine (Park et al, 2014). However, construction and testing of the B. methanolicus strains M168-20_RaiP Sj , M168-20_RaiP Ps , and M168-20_RaiP Tv (Table 4), based on the L-lysine-over producing mutant M168-20 (Brautaset et al, 2010), did not result in any improved 5AVA production (data not shown).…”
Section: Expression Of the Davab-encoding Genes Resulted In No 5ava Biosynthesis In B Methanolicusmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the precursor levels in the B. methanolicus strains should not be a limiting factor for production of 5AVA. The RaiP-mediated production is mainly utilized in the L-lysine bioconversion approach, utilizing E. coli strains as whole-cell biocatalysts (Cheng et al, 2018(Cheng et al, , 2020(Cheng et al, , 2021 where high concentrations of the precursor were used; for example, the molar yield of 0.942 was obtained from 120 g l −1 Llysine (Park et al, 2014). However, construction and testing of the B. methanolicus strains M168-20_RaiP Sj , M168-20_RaiP Ps , and M168-20_RaiP Tv (Table 4), based on the L-lysine-over producing mutant M168-20 (Brautaset et al, 2010), did not result in any improved 5AVA production (data not shown).…”
Section: Expression Of the Davab-encoding Genes Resulted In No 5ava Biosynthesis In B Methanolicusmentioning
confidence: 99%
“…Recently, an artificial synthetic pathway for the biosynthesis of 5AVA in E. coli was developed, consisting of three steps: conversion of L -lysine to α-ketolysine via RaiP, decarboxylation of α-ketolysine to produce 5-aminopentanal via α-ketoacid decarboxylase, and oxidation of 5-aminopentanal to 5AVA via aldehyde dehydrogenase. The expression of the artificial pathway resulted in a yield increase of 774% compared to the single gene pathway ( Cheng et al, 2021 ). This approach is potentially a feasible strategy we have shown in our study that E. coli -derived PatD is active as a 5-aminopentanal dehydrogenase in B. methanolicus and participates in 5AVA biosynthesis (see Section “The PatA Pathway Supports 5AVA Accumulation in B. methanolicus ).…”
Section: Resultsmentioning
confidence: 99%
“…In the first pathway, l -lysine is converted to 5AVA by l -lysine-α-oxidase (RaiP) from Scomber japonicas by oxidative deamination and a spontaneous decarboxylation step (Cheng et al, 2020). Recently, an alternative synthetic route was established starting with RaiP, but the intermediate 2-keto-6-aminocaproate is converted by α-ketoacid decarboxylase (KivD) from Lactococcus lactis and aldehyde dehydrogenase (PadA) from Escherichia coli to 5AVA ( Cheng et al, 2021 ). The second pathway to 5AVA combines oxidative decarboxylation by l -lysine monooxygenase (DavA) using molecular oxygen followed by desamidation by γ-aminovaleramidase (DavB) from P. putida ( Adkins et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The monomers of polyamides are primarily dicarboxylic acids, diamines, lactams, and ω-amino acids ( Radzik et al, 2019 ). Examples of these main platform chemicals range from succinate ( Zhang et al, 2009 ), glutarate ( Zhao et al, 2018 ), to adipate ( Wang F. et al, 2020 ) for dicarboxylic acids; from putrescine, cadaverine ( Rui et al, 2020 ; Xue et al, 2020 ), to 1,6-hexanediamine for diamines; from δ-valerolactam ( Zhang et al, 2017a ), to ε-caprolactam ( Thompson et al, 2020 ) for lactams; from 3-hydroxybutyrate ( Atakav et al, 2021 ; Mierziak et al, 2021 ; Schmid et al, 2021 ), 2-hydroxybutyrate ( Tian et al, 2021 ), to 3-hydroxyhexanoate ( Harada et al, 2021 ) for hydroxyl acids; and from 4-aminobutyrate, 5AVA ( Cheng et al, 2021b ), to 6-aminocaproate ( Turk et al, 2016 ) for ω-amino acids. In this respect, also 5AVA ( Adkins et al, 2013 ) and δ-valerolactam ( Xu et al, 2020 ) are attractive C5 platform chemicals for the production of biopolyamides from renewable biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Cheng et al proposed that the titer of 5AVA could be improved to 29.12 g/L by adding 4% (v/v) ethanol and 10 mM H 2 O 2 ( Cheng et al, 2018b ). Independently, a three-step route based on RaiP, α-ketoacid decarboxylase (KivD) from Lactococcus lactis , and aldehyde dehydrogenase (PadA) from Escherichia coli ( E. coli ) was established in E. coli with 5AVA titer up to about 52.24 g/L ( Cheng et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%